Effect Prebiotic on Growth and Feed Retension of Tilapia) - Achmad Noerkhaerin Putra (Jurnal Perikanan dan Kelautan, 2017)
The addition of prebiotics to the diet can increase the availability of enzyme in thedigestive tract of fish. This study aimed to evaluate the effect of the different dose ofprebiotic to the growth and nutrition retention of tilapia. Four treatment and 3 replicates,namely: control (0% prebiotic), 1% prebiotic, 2% prebiotic and 3% prebiotic were usedin the experiment. The results showed that the addition of prebiotics in fed can promotebetter tilapia growth and nutrition retention compared to control. The highest specificgrowth rate was found in 2% prebiotic (4.10%), followed by 1% prebiotic (3.83%), 3%prebiotic (3.54%) and the lowest was in the control (3.34%) (P<0.05). The addition of2% prebiotics in the diet showed best result on promoting tilapia growth, feed efficiencyand nutritent retention